How did consumers’ self-protective behavior formed during the COVID-19 pandemic? - Xue, Hu; Jin, Shanshan; Wu, Qianrong; Geng, Xianhui (Frontiers in Psychology, 2023)
Introduction This study explored the formation mechanism of consumers’ self-protective behavior during the COVID-19 pandemic, which is very important for policy settings to regulate consumer behavior. Based on the basic framework of the Protective Action Decision Model (PADM), this study analyzed the formation mechanism of consumers’ self-protective willingness from the perspective of risk information, and explained the deviation between consumers’ self-protective willingness and behavior from the perspective of protective behavior attributes. Methods Based on 1,265 consumer survey data during the COVID-19 pandemic, the empirical test was carried out. Results and Discussion The amount of risk information has a significant positive impact on the consumers’ self-protective willingness, where the credibility of risk information plays a positive moderating role between them. Risk perception plays a positive mediating role between the amount of risk information and the consumers’ self-protective willingness, and the positive mediating effect of risk perception is negatively moderated by the credibility of risk information. In the protective behavior attributes, hazard-related attributes play a positive moderating role between the consumers’ self-protective willingness and behavior, while resource-related attributes play the opposite role. Consumers pay more attention to hazard-related attributes than resource-related attributes, and they are willing to consume more resources to reduce risk.